A cointegration and causality analysis of copper consumption and economic growth in rich countries - Jaunky, Vishal (Pergamon Press, 2013)
The paper examines the copper consumption-economic growth nexus for 16 rich economies from the period 1966 to 2010. Various generations of panel unit root and cointegration tests are applied. Both series are found to be integrated of order one. Evidence of cointegration is found especially when controlling for breaks and long-run cross-sectional dependence. Causality is investigated using a vector error-correction mechanism (VECM) framework. At individual level, unidirectional causality running from economic growth to copper consumption is unraveled for Finland, France and UK in the long-run. Unidirectional causality is also found running from copper consumption to economic growth for Spain. Long-run bi-directionality between economic growth and copper consumption is found for Belgium, Greece, Italy, Japan and South Korea. The neutrality hypothesis holds for Australia, Austria, Canada, Netherlands, Portugal, Sweden and USA in the long-run. Taken as a whole, panel causality test reveals a long-run unidirectional causality running from economic growth to copper consumption. © 2013 Elsevier Ltd.